A Rare Case of Cerebral Abscess due to with Native Aortic Valve Infective Endocarditis and Pyogenic Liver Abscess - Zoheb Irshad Sulaiman DO; Divisha Sharma MD; Juan Rivera Salva MD; Johnathon Rast MD; Hasan Samra MD FCAP; Gina Askar MD (SAGE Publishing, 2024)
Fusobacterium nucleatum is a commensal pathogen typically found in the oral cavity, digestive tract, and urogenital system which has been associated with Lemierre's syndrome, periodontal diseases, sinusitis, endocarditis, and intra-abdominal and brain abscesses. Our case is of a 62-year-old male who presented with headaches, nausea, and vision loss. Brain imaging identified a right occipito-parietal brain abscess. Following surgery and abscess drainage, Fusobacterium nucleatum was isolated from intraoperative cultures, and the infectious disease service was consulted for antibiotic recommendations. Additional history uncovered that he had also been experiencing night sweats, generalized weakness and 40-pound weight loss for 2 months, and had a prior history of colon polyps and diverticulitis. Furthermore, the patient disclosed having substandard oral hygiene practices, particularly in relation to the care of his dental appliances. Despite negative blood cultures, suspicion for hematogenous seeding was high. Imaging ruled out periodontal disease, but identified a colovesical fistula and liver abscesses, indicating potential translocation of bacteria via portal circulation to his liver. Echocardiogram workup revealed a 1-cm mobile vegetation on the aortic valve. His course was complicated by breakthrough seizures, renal failure, and drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome, and he ultimately completed 16 weeks of antibiotics. This case illustrates an uncommon presentation of brain abscess in an immunocompetent adult, with a prior episode of diverticulitis as the probable primary infection source, leading to development of a colovesical fistula and bacterial dissemination to the liver, heart, and brain. It highlights the importance of a comprehensive diagnostic approach, including consideration of atypical pathogens in immunocompetent adults.